Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00520-013-1860-1
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide prescribing patterns in the palliation of symptomatic inoperable malignant bowel obstruction patients at a single US academic hospital

Abstract: These data possibly suggest that the MBO patients on the medical vs. surgical services are distinct patient populations. MBO patients on the medical service trended to receive higher cumulative doses and have a decreased overall survival compared with surgical patients. Consequently, future studies should possibly consider these distinct study groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The 57 observational studies 45 101 reported on the treatment of 12,587 patients, 92% of which were patients with malignant bowel obstruction. Of these palliative patients, 27% underwent surgery for their obstruction (initially or after temporary stenting) and 73% were inoperable.…”
Section: Resultsmentioning
confidence: 99%
“…The 57 observational studies 45 101 reported on the treatment of 12,587 patients, 92% of which were patients with malignant bowel obstruction. Of these palliative patients, 27% underwent surgery for their obstruction (initially or after temporary stenting) and 73% were inoperable.…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of the fluid secretion-absorption balance of the intestine is a key pathophysiological change in MBO. 16 Generally, the pathophysiology of MBO can be divided into 5 processes 18 : (1) Bowel obstruction gives rise to intestinal distension, resulting in increased intestinal secretion and malabsorption of water and electrolytes in the obstructed bowel segment. (2) Secreted intestinal fluid further accumulates, and the intestinal tract moves in an abnormally uncoordinated manner, further stimulating contraction of the intestinal lumen and greater proximal distension.…”
Section: Pathophysiologymentioning
confidence: 99%
“…However, a paucity of welldesigned randomized studies has left optimal timing of SSA initiation, dosing, and duration of therapy open for interpretation, warranting additional exploration with comparative trials with validated end points. 27 Obita et al 28 conducted a comprehensive systematic review of seven randomized controlled trials (RCTs) comparing SSA (eg, octreotide 200 to 900 mg SC twice a day to three times a day or 300 mg/d via continuous infusion) to placebo or other pharmacologic agents in MBO. The authors identified five trials with low-level evidence suggesting a benefit of SSAs, whereas two trials with higher-level evidence failed to demonstrate benefit.…”
Section: Nonoperative Proceduresmentioning
confidence: 99%